(untitled) (Research, Society and Development, 2025)
The presence of fluoride in the water supply and toothpastes shows that the prevalence of tooth decay in Brazil has decreased in its incidence, and the correct choice of toothpaste can contribute to the reduction of the disease. The choice of toothpaste is sometimes made empirically, for socioeconomic reasons, or by influences from third parties, such as digital influencers or the pharmaceutical industry itself through huge campaigns on television and social networks. Some still question the benefits of fluoride, influencing qualities, and promoting information that can generate in our individuals a tendency to buy toothpaste without fluoride, which can lead to an increase in the rate of tooth decay in this population. The objective of this study was to investigate through a self-administered questionnaire that classifies patients seen at a teaching clinic of a dentistry university in Vale do Paraíba used to choose their toothpaste. The data obtained revealed that the vast majority of (many) respondents choose toothpaste based on the commercial brand. It is concluded that the dentist’s professional advice plays a fundamental role in guiding and indicating to the patient the use and purchase of toothpastes and for this it is necessary that there is constant updating of professionals and that there are also oral health actions in various places such as neighborhoods, schools and companies.